Management of Dysgeusia related to Cancer: A Systematic Review - Munankarmi, Durgeshwori (Journal of Lumbini Medical College, 2017)
Introduction: Taste change due to cancer is a notorious side effect, adversely affecting appetite and weight. Even though taste change or dysgeusia is one of the major causes of poor nutritional status in cancer survivors, it is not addressed as a significant problem and is often left untreated. The main purpose of this review is to explore current knowledge of pharmacological and behavioral interventions for the treatment of cancer related taste change.Methods: This systematic review was conducted in accordance with PRISMA guidelines to identify original articles on taste change. Multiple databases including; Scopus, Medline, EMBASE, CINAHL, and all databases via Pro quest were searched for original articles or studies related to taste change caused by cancer or its treatment. Relevant articles were subjected to a full text evaluation and assessed by Critical appraisal skills program (CASP) guidelines and the Effective public health practice project (EPHPP) instrument. Results: The search revealed 12 eligible studies, six of which were randomized controlled trials. Most of the studies used a standardized validated tool to measure taste change. Dysgeusia is common in cancer, 14 to 100% cancer patient report it. Pharmacological management with zinc remains inconclusive as one study reports it as beneficial and two other studies reported null effect. Few studies suggested dietary modifications such as use of sugary, salty foods that are helpful to reduce the effect of dysgeusia.Conclusion: Dietary counseling and informing the patient well about self-care strategies before treatment has consistently shown positive results on taste change, with strong statistical power. Other potential treatments for dysgeusia such as zinc, amifostine, and megestrol acetate gave inconsistent results. Journal of Lumbini medical College Vol 5, No 1, Jan-June 2017, Page: 3-12DOI: https://doi.org/10.22502/jlmc.v5i1.110